Hyperprocalcitonemia as a clinical prognosis in septic patients of private hospitals in the city of Cuenca–Ecuador - Ledesma Pacurucu, Diego Enrique; Espinosa, Hermel Medardo; Flores Montesinos, Carlos Enrique; Espinosa Martin, Lizette; Torres, Zoila Katherine; Aspiazu Hinostroza, Karla Alexandra; Martínez Salazar, Patricia Michelle (Kasmera, 2020)
Procalcitonin, an acute phase’s reactant, enables to establish sepsis-diagnosis’-patients status, bringing the possibility of associate it with its prognosis. The aim of this study was to determine the clinical prognosis of hyperprocalcitonemia in septical patients of private hospital centers in Cuenca–Ecuador. The study was cross-sectional, the sample were 207 patients. Data was analyzed with SPSS statistical program (25.0); analysis was done through descriptive statistic; association through Odds Ratio (OR), confidence interval (95%), considering statiscally significant values with p <0.05. Severe hyperprocalcitonemia prevalence was 63.29%, average age 67.25±19.07 years old; male sex prevailed 57% and half-blood ethnic group. A statistical association between severe hyperprocalcitonemia and longer hospital stay (≥15 days) was shown OR: 2.41 (CI 95% 1.11–5.19 p: 0.015); likewise, with in-hospital mortality OR: 9.37 (CI 95% 4.31–20.37 p: <0.000). Association was determined, but statistical significance with presence of comorbidities was not OR: 1.35 (CI 95% 0.69–2.64 p:0.243). Severe hyperprocalcitonemia was shown in almost 2/3 of patients, and there was an association with mortality increase and hospital stay